Global Public Policies and Programs : Implications for Financing and Evaluation - Gerrard, Christopher D.; Ferroni, Marco; Mody, Ashoka (Washington, DC: World Bank, 2013)
These are the proceedings from a World Bank workshop on global public policies, and programs, assembled from transcripts, and accompanying papers. The combination of market failure, and limited institutional capacity to influence economic, and social change across national borders, underlies public discontent with aid. This formed the basis for discussions, looking for new approaches to the development assistance business, taking into account the growing integration of the global economy, and arguing that, beyond supporting market-friendly reforms, aid strategies must be designed to overcome social, and structural constraints to sustainable development. The broad range of cases examined include efforts to craft commonly accepted standards for the design, and operation of large dams; they address issues of global financial instability; explore the implications of intellectual property rights protection for developing countries; describe the promotion of international agricultural research; probe the implementation of international public health programs; and, identify the dilemmas associated with the financing, and evaluation of global public policies, and programs. Such programs have become center stage because of irreversible processes associated with globalization, and, similar initiatives will dominate the development scene for years to come.